2008
DOI: 10.1080/08880010701774132
|View full text |Cite
|
Sign up to set email alerts
|

Early Death in Children With Acute Lymphoblastic Leukemia: Does Malnutrition Play a Role?

Abstract: The study aim was to correlate malnutrition and early death in children with acute lymphoblastic leukemia (ALL). A study was conducted in 100 consecutive children with ALL. An analysis included clinical and laboratory parameters as well as co-morbidity factors. Forty patients were standard risk and 60 high risk. Multivariate analysis showed variables of statistical importance, including female gender (p 010), ALL high-risk (p 04), and infection (p 036). Malnutrition (p 1.0) and poverty (p 0.5) did not influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…In Pakistan, underweight children with ALL were at higher risk of relapse and mortality compared with normal-weight children ( 71 ). Although the relation between weight/body size and survival is supported across HICs and LMICs by meta-analyses and review articles ( 68 , 72 , 73 ), several studies have concluded that there is no relation between weight/body size and survival ( 74–77 ). The reason for the discrepancy in results is likely due to the different classification of malnutrition based on weight and body size, and this highlights the need for studies to assess the link between FM and FFM and survival in children with cancer in LMICs.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…In Pakistan, underweight children with ALL were at higher risk of relapse and mortality compared with normal-weight children ( 71 ). Although the relation between weight/body size and survival is supported across HICs and LMICs by meta-analyses and review articles ( 68 , 72 , 73 ), several studies have concluded that there is no relation between weight/body size and survival ( 74–77 ). The reason for the discrepancy in results is likely due to the different classification of malnutrition based on weight and body size, and this highlights the need for studies to assess the link between FM and FFM and survival in children with cancer in LMICs.…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…The main effect of malnutrition on treatment, is due to an alteration of the biodisponibility of antineoplastic drugs, which is achieved through the following mechanisms: a) changes in absorption, eg for drugs like methotrexate and 6 mercaptopurine, b) the decreased drug transport by the reduction or lack of plasmatic proteins, and c) by decrease in hepatic metabolism of the antineoplastic mainly caused by a lack of enzymatic activity by cytochrome P450. [28][29][30][31][32][33][34][35][36][37] Furthermore. highlight the importance of studying on the subject of how malnutrition affects the prognosis of patients with ALL, because in some of the studies did not allow conclusions to determine whether the association exists in some of these studies were given the limitations by factors such as inadequate sample size, the inconsistency in how to assess the nutritional status between studies, and also have not been studied other possible complications in the evolution of these patients, such as relapse, abandonment in the treatment, among others.…”
Section: Prognosismentioning
confidence: 99%
“…[8,29,41] According to Reilly J, et al, There are three mechanisms that explain the direct influence of malnutrition on survival of patients with ALL: The first, means that if there is a greater severity of malnutrition, there will be a greater severity of leukemia this because as we know, malnutrition is a surrogate marker of the disease state, the second mechanism is related to immune system dysfunction that occurs in malnourished patients, which would cause increased susceptibility to potentially serious infections could lead to the death of the patient, and finally, a mechanism related to adipose tissue, which has as one of its main functions being a facilitator to take place the pharmacokinetics of many anticancer drugs, this tissue is functionally and structurally altered in malnutrition, resulting in a lower effective antineoplastic drugs and greater toxicity and that both could be potential factors sufficient to endanger the patient's life, however this mechanism has been studied by other authors who found no such effect. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Therefore, it is believed that malnutrition alone is a major factor in poor prognosis and survival of patients with ALL, however, it is noteworthy that most of the studies performed, are from developed countries and / or where it is mainly evaluated the impact of malnutrition on long-term survival, so it is necessary to know whether the association also exists in developing countries, because these populations have certain characteristics, such as frequencies malnutrition and deaths occur primarily during the first year of treatment much higher, and it also has been reported as one of the main obstacles to improved survival rates in patients with ALL. [39,[42][43][44][45]…”
Section: Survivalmentioning
confidence: 99%
See 2 more Smart Citations